MAXIMUM POWER POINT TRACKING OF PHOTOVOLTAIC SYSTEM - DAT, NGO TIEN (Universiti Teknologi Petronas, 2011)
Renewable energy sources plays an important role in electricity generation. Various renewable energy sources like wind, solar, geothermal, ocean thermal, and biomass can be used for generation of electricity and for meeting our daily energy needs. Energy from the sun is the best option for electricity generation as it is available everywhere and is free to harness. On an average the sunshine hour in Malaysia is about 9 hours annually also the sun shine shines in Malaysia for a whole 12 months in a year. Electricity from the sun can be generated through the solar photovoltaic modules (SPV). The SPV comes in various power output to meet the load requirement. Maximization of power from a solar photo voltaic module (SPV) is of special interest as the efficiency of the SPV module is very low. Every photovoltaic (PV) array has an optimum operating point, called the maximum power point, which varies depending on cell temperature, the insolation level and array voltage. A peak power tracker is used for extracting the maximum power from the SPV module. The function ofMPPT is need to operate the PV array at its maximum power point. The present work describes the maximum power point tracker (MPPT) for the SPV module connected to a resistive load. The simulation studies are carried out in MATLAB/SIMULINK. The design of the MPPT is proposed utilizing a boostconverter topology. Many algorithms have been proposed, however, two algorithms, the perturb-and-observe (P&O) method, and incremental-conductance (IC) claimed by many in the literature to be inferior to others, continues to be by far the most widely used method in commercial MPPT ofPV.